Nome Circle Bandstand with Oregon State Building in the background, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Oregon State Building, Alaska-Yukon-Pacific Exposition, Seattle, Wash., 1909 Publisher: Portland Post Card Co. (no. 5362) PH Coll 78.50 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number